Pengaruh Model Pembelajaran Discovery Learning Berbantuan Desmos terhadap Pemahaman Konsep Materi Persamaan Garis Lurus - Fhela Vhantoria Ningrum; Fayza Natarina Nur Azzahra (Universitas Muhammadiyah Kotabumi, 2025)
The low the skill level eight grade students at MTs Negeri 1 North Lampung to understand the concept of linear equations result from the implementation of learning models. The learning model that is tought to influence the understanding of the concept of linear equations is the Desmos-assisted Discovery Learning learning model. Its purpose is in the present research was to identify if the Desmos-assisted Discovery Learning model impacts student’s understanding of the concept of linear equations among eighth-grade students at MTs Negeri 1 Lampung Utara. This study applied a Quasi-Experimental Design featuring a Nonequivalent Control Group Design. The population involved in this research consisted of all eighth-grade students at MTs Negeri 1North Lampung. The sampling technique applied was simple random sampling was conducted with clasThe low the skill level eight grade students at MTs Negeri 1 North Lampung to understand the concept of linear equations result from the implementation of learning models. The learning model that is tought to influence the understanding of the concept of linear equations is the Desmos-assisted Discovery Learning learning model. Its purpose is in the present research was to identify if the Desmos-assisted Discovery Learning model impacts student’s understanding of the concept of linear equations among eighth-grade students at MTs Negeri 1 Lampung Utara. This study applied a Quasi-Experimental Design featuring a Nonequivalent Control Group Design. The population involved in this research consisted of all eighth-grade students at MTs Negeri 1North Lampung. The sampling technique applied was simple random sampling was conducted with class VIII A and VIII B selected as the samples. The essay test instrument was given prior to the treatment at the start of the learning process and again after the treatment at the end of the learning process. According to the results of to the t-test analysis, the value of, and indicating that thus is rejected, and the alternative is accepted. Consequently implies that the Desmos-assisted Discovery Learning model has a significant effect on students’ learning outcomes understanding of the concept of linear equations in class VIII at MTs Negeri 1 North Lampung VIII A and VIII B selected as the samples. The essay test instrument was given prior to the treatment at the start of the learning process and again after the treatment at the end of the learning process. According to the results of to the t-test analysis, the value of, and indicating that thus is rejected, and the alternative is accepted. Consequently implies that the Desmos-assisted Discovery Learning model has a significant effect on students’ learning outcomes understanding of the concept of linear equations in class VIII at MTs Negeri 1 North Lampung